Differential Inhibition of Common Bacterial Species by Extracts of Three Fruits Using Different Solvents - Mahmood, S.; Bashir, S.; Farzana, K.; Akram, M. R.; Abrar, M. A.; Murtaza, G. (2012)
The antibacterial activities of the chloroform, methanol, petroleum ether and water extracts of the fruits of loquat (Eriobotrya japonica Lindl.), fig (Ficus carica L.) and date palm (Phoenix dactylifera L.) were compared against Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus using the disc diffusion method. Methanol extract of the fruits exhibited the highest antibacterial activity while a reduced sensitivity of all bacterial species was observed for chloroform extract. The minimum bactericidal concentration and differential susceptibility of bacterial species were determined for various dilutions (1000, 500, 250 and 125 μg mL-1) of methanol extract from each fruit. Methanol extracts from E. japonica and P. dactylifera were found to be more effective (P≤ 0.05) against E. coli. On the other hand, growth of S. aureus and E. coli was significantly (P≤ 0.05) inhibited by F. carica. A consistently lower susceptibility of P. aeruginosa indicated its capability for developing resistance against various bactericidal substances. The 500 μg mL-1 dilution of methanol extract can be considered as the minimum bactericidal concentration for all fruits. Bactericidal activities displayed by all fruits also signified their remarkable potential for exploration of effective natural antibacterial agents against common pathogenic bacteria.
Keywords: Bacteria; Fruit extracts